Poste planche - Post, mail, historical, airmail, uniforms, in France... - EN NOIR & BLANC (Wikimedia Commons, 2013)
Notice iconographique issue de Wikimedia Commons. Titre: Poste planche - Post, mail, historical, airmail, uniforms, in France, etc. - Public domain illustration from Larousse du XXème siècle 1932. Poste planche - Post, mail, historical, airmail, uniforms, in France, etc. - Public domain illustration from Larousse du XXème siècle 1932 Éditions Larousse is a French publishing house specialising in reference works such as dictionaries. It was founded by Pierre Larousse and its best-known work is the Petit Larousse.
Droits : Licence Creative Commons Zero, Public Domain Dedication via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie